Increasing number of fraudulent activities in MFS industry and the role of compliance management Service in order to reduce it: a case analysis through bKash and relevant issues - Hossain, Md. Zubair (Brac University, 2021)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2021.